Truth, dare or promise : art and documentary revisited - Daniels, Jill; McLaughlin, Cahal; Pearce, Gail (Cambridge Scholars Publishing, 2013)
"Truth, Dare or Promise: Art and Documentary Revisited reflects on the ways that artists and filmmakers address the innovations and limitations of producing and exhibiting their work. Ranging from community collaboration to individual interpretation, and from gallery installation to cinematic screening, exploring the differences and overlaps between definitions and methodologies. With an international reach, including contributors who are both practitioners and theorists, this book maps out developments in art and documentary, covering themes that include explorations of personal experience and representations of the past, while examining interactive galleries and the cinematic space"--Provided by publisher.